1975
DOI: 10.1139/v75-081
|View full text |Cite
|
Sign up to set email alerts
|

13C Nuclear Magnetic Resonance Studies. 45. The 13C Spectra of Some β,γ Unsaturated Polycyclic Ketones

Abstract: . Can. J. Chem. 53,581 (1975).The I3C spectra of several P,y unsaturated polycyclic ketones have been recorded to examine the shielding differences for all carbons relative to those for their saturated analogs and the parent olefins. The variations of the sp2 carbon shieldings provide qualitative evidence for the existence of homoconjugative interactions between the olefinic and carbonyl groups in the ground state. J Similar evidence of interaction between y,6 double bonds and carbonyl groups was found from ,s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

1978
1978
1996
1996

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…The alcohols were prepared from 7-tertbutylnorbornadiene (36) by the methods of Baird and Surridge (17), the only modification being hydroboration of syn-7-tertbutylnorbornene (37) with BMS rather than with 9-borabicyclo[3.3.l]nonane (9-BBN) -an expedient that gave an improved yield of 38.…”
Section: A1203mentioning
confidence: 99%
See 1 more Smart Citation
“…The alcohols were prepared from 7-tertbutylnorbornadiene (36) by the methods of Baird and Surridge (17), the only modification being hydroboration of syn-7-tertbutylnorbornene (37) with BMS rather than with 9-borabicyclo[3.3.l]nonane (9-BBN) -an expedient that gave an improved yield of 38.…”
Section: A1203mentioning
confidence: 99%
“…Spectroscopic assignments for the unsaturated ketones 18, 27, and 32 prepared in the present work are included in Table 7, together with those for 5-norbornen-2-one (24) (36). The introduction of AS B.7-unsaturation into 2-norbornanones has been observed preiiobsly to lead to shielding of the carbonyl carbon; it has also been observed that C-6 is shielded and C-5 is deshielded with respect to the corresponding olefins (29).…”
Section: C Nuclear Magnetic Resonance Spectramentioning
confidence: 99%
“…En particulier les dtplacements chimiques B champ fort de rarbones situts en y de groupes mtthyles et tclipsts par ceux-ci sont dus des interactions steriques (4). L'influence du groupe hydroxyle a t t t ttudite dans les systkmes bicycliques conformationnellement fixes (strie bicyclo[2.2.1]-heptanique ou -[2.2.2]octanique, strie de l'adamantane) ou peu flexibles (strie bicyclo[3.2.1 Ioctanique) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Dans des series de dtcalols (17) et de sttroides (17,18), l'influence du groupe OH sur les carbones en y et en 6 de ce substituant a aussi t t t ttudite; des effets y de -3.3 B -7.3 ppm ont pu ainsi Etre mis en tvidence.…”
Section: Introductionunclassified
“…The combined extracts were dried over MgS04. Evaporation of the solvent gave a yellow oil (6.3 g, 70%) that was a 1:l mixture of two major components, by glc analysis (DEGS), which were identified as 10 and 11 by I3cmr (10). The crude product was subjected to flash chromatography 20:80) to remove traces of minor impurities before the methylation step.…”
Section: Bicyclo[32 L]oct-6-en-2-and -3-ones (10 11)mentioning
confidence: 99%